2020
DOI: 10.1007/s42979-020-00165-4
|View full text |Cite
|
Sign up to set email alerts
|

Fake News Detection Using a Blend of Neural Networks: An Application of Deep Learning

Abstract: Fake news and its consequences carry the potential of impacting different aspects of different entities, ranging from a citizen's lifestyle to a country's global relations, there are many related works for collecting and determining fake news, but no reliable system is commercially available. This study aims to propose a deep learning model which predicts the nature of an article when given as an input. It solely uses text processing and is insensitive to history and credibility of the author or the source. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Decision tree algorithm appears to produce the most consistent results with minimal standard deviation. In paper (Agarwal et al 2020), feed forward neural networks which are developed using deep learning used to identify the fake news on social media which gives an accuracy of 97%. In paper (Ahmad et al 2020), Random forest and SVM(Support Vector Machine) machine learning algorithms are implemented to identify the fake news with accuracy of 91% and 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Decision tree algorithm appears to produce the most consistent results with minimal standard deviation. In paper (Agarwal et al 2020), feed forward neural networks which are developed using deep learning used to identify the fake news on social media which gives an accuracy of 97%. In paper (Ahmad et al 2020), Random forest and SVM(Support Vector Machine) machine learning algorithms are implemented to identify the fake news with accuracy of 91% and 96%.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results indicated that the J48 algorithm achieved the highest accuracy compared with the other AI models. Further, the authors in [16] described a deep learning model on a Kaggle fake news dataset. They performed text preprocessing by using word embedding (GloVe) to construct a vector space of words and created a linguistic relationship.…”
Section: Related Workmentioning
confidence: 99%
“…Whereas, in [ 30 ] authors proposed a technique for fake news detection by combining text mining techniques and supervised artificial intelligence algorithms, where the result shows that the best mean values in terms of precision, accuracy, recall, and f-measure have been obtained from the decision-tree, CVPS, ZeroR algorithms. In [ 31 ], the authors adopted a deep neural network(Convolution and Recurrent neural network) for the feature extraction process to predict fake news. Whereas, credible web sources are analyzed by [ 32 ] for the fake news prediction.…”
Section: Related Workmentioning
confidence: 99%